Proses Registrasi Visitor pada Event Indonesia International Hospital Expo 2018 - Anisa Fitri; Etty Kongrat (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
The 31st Indonesia International Hospital Expo has been held in Jakarta Convention Center (JCC), in October 17-20, 2018. This annual event is hosted by PT Okta Sejahtera Insani. This event was held successfully with a total visitors 40,452. This number exceeds the target of 40,000 visitors. One of an important aspect for a successful event is registration. Registration in this research is using two methods to register, onsite and online registration. The first method is online registration, which is using website for register. The second method is onsite registration, which is register directly during event. Visitors who come to this event are government officers, medical doctors, hospital owner, hospital manager, CEO/COO hospital, hospital quality control, etc.